Identification and Diversity of Organisms in the Lake Toba Area (Jurnal Pendidikan IPA Indonesia, 2019)
This research is an explorative research/Land-Based Survey. The purpose of this research is to identify an organism in the Lake Toba water to see organism diversity in the area of Lake Toba, and some factors which influence the kind and diversity of organism in Lake Toba. This research was conducted by using methods of a trap in May 2016 until April 2017 in three regencies of Lake Toba Area, including Samosir, Simalungun, and Porsea Regency. The result of the research showed that the organisms found in the waters of Lake Toba were Plakton, Macrozoobentos, and Nekton. The index of macrozoobenthos diversity in three regencies are categorized into low. The highest value of diversity was in Samosir Regency (1,6) then followed by Tobasa (1,5), and Simalungun (0,43). The value of plankton diversity index in three regencies are; Samosir (2,47), Tobasa (1,41), and Simalungun Regency(1,63). The index of fish diversity in three regencies was categorized into low; Samosir (1,97), Tobasa (1,16), and Simalungun Regency (1,61). In those three districts, there were 25 species of plankton, 12 species of macrozoobenthos and 8 species of fish. The change of the environmental condition influenced the diversity of animal. The research suggests that the need for conservation as the management planning to cope with the environmental condition to maintain the quality of Lake Toba environment.